Zwierzęta w interpretacji symbolicznej "Formulae spiritalis intellegentiae" Eucheriusza z Lyonu - Skibiński, Tomasz (Vox Patrum, 2024)
The subject of this article is the analysis of the symbolic interpretation of animals as presented by Eucherius of Lyon in his work Formulae spiritalis intellegenatiae. The article examines Eucherius’s interests and knowledge in the field of symbolic interpretation of animals, the sources he used, and the content of his interpretation. The primary source of the research are Formulae spiritalis intellegentiae, which is compared primarily with another exegetical work, Instructiones. The research reveals that Eucherius possesses a fundamentally good knowledge of biblical animals, largely indebted to the sources he utilized. His interpretation addresses several fundamental themes: theological issues, where the author interprets animals as symbols of Christ, the Holy Spirit, or, in opposition, the devil (demons, idols). Anthropological interpretations are also frequent, wherein animals symbolize people judged positively or negatively for moral or doctrinal reasons. Animals can also symbolize Scripture and types of its interpretation. Eucherius’s works are addressed to his sons, Salonius and Veranius, who later became bishops. The works were also intended for a wider audience, and it is evident that Eucherius assumed a certain level of proficiency and familiarity with the Holy Scripture and its interpretation among his readers, hence he did not see the need to provide overly detailed or fundamental explanations.